Anion insertion enhanced electrodeposition of robust metal hydroxide/oxide electrodes for oxygen evolution - Zhenhua Yan (Nature Portfolio, 2018)
Electrodeposition provides a facile fabrication means for electrochemical devices but weak substrate-deposit interactions cause poor performance. Here, authors utilize anion insertion within graphitic layers to improve the material interfaces and construct highly active O2-evolving electrocatalysts.